The potential and challenges of TREM2-targeted therapy in Alzheimer’s disease: insights from the INVOKE-2 study - Ma, Ya-nan; Hu, Xiqi; Karako, Kenji; Song, Peipei; Tang, Wei; Xia, Ying (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) is a severe neurodegenerative disorder with a growing global burden. With the rising incidence of AD, the need for novel therapeutic targets has become increasingly critical. TREM2, a receptor expressed on microglial cells, plays a crucial role in modulating neuroinflammation and clearing pathological substrates, making it a promising candidate for AD therapy. However, the recent clinical trial INVOKE-2 failed to demonstrate significant clinical benefits of the TREM2-targeted antibody AL002, raising doubts about the efficacy of TREM2-targeted methods. This article examines the role of TREM2 in AD pathogenesis, evaluates potential reasons for the disappointing outcomes of the INVOKE-2 trial, and discusses future directions for TREM2-based therapies. Factors such as treatment timing, dosage optimization, patient genetic variability, and combination therapy strategies are identified as critical determinants of therapeutic success. Future studies should aim to refine treatment strategies, identify precise indications, and explore the potential for combination therapies to enhance efficacy.